Effects of resistance exercise, collagen ingestion and circulating oestrogen concentration on collagen synthesis in a female athlete: a case report - Lee, J.; Tang, J. C. Y.; Dutton, J.; Dunn, R.; Fraser, W. D.; Enright, K.; Clark, D. R.; Stewart, C. E.; Erskine, R. M. (Experimental Physiology, 2025)
We investigated the effects of resistance exercise (RE), hydrolysed collagen (HC) ingestion and circulating oestrogen concentration on collagen synthesis in a naturally menstruating female CrossFit athlete. In a double-blind, randomised cross-over design, the participant (36 years; height 1.61 m; mass 82.6 kg) consumed 0 or 30 g HC prior to performing back-squat RE when endogenous circulating oestrogen concentration was low (onset of menses, OM) and high (late follicular phase, LF) during two consecutive menstrual cycles. Ten 5-mL blood samples were collected during each of the four interventions to analyse concentrations of serum 17ß-oestradiol, and biomarkers of type I collagen turnover, that is serum procollagen type I N-terminal propeptide (PINP, a biomarker of collagen synthesis) and plasma ß-isomerised C-terminal telopeptide of type I collagen (ß-CTX, a biomarker of collagen breakdown), as well as the serum concentration of 18 collagen amino acids. 17ß-Oestradiol concentration was 5-fold higher at LF (891 ± 116 pmol L-1) than OM (180 ± 13 pmol L-1). The PINP concentration × time area under the curve (AUC) was higher in the 30 g HC OM intervention (201 µg L-1 h) than the 30 g HC LF (144 µg L-1 h), 0 g HC OM (151 µg L-1 h) and 0 g HC LF (122 µg L-1 h) interventions. ß-CTX concentration decreased 1.4-fold from pre-RE to 6 h post-RE in all interventions. Thus, high circulating oestrogen concentration was associated with lower collagen synthesis following RE in this female athlete. Ingesting 30 g HC, however, augmented the collagen synthesis response at LF and particularly at OM.